2016
DOI: 10.1128/aem.00773-16
|View full text |Cite
|
Sign up to set email alerts
|

Next-Generation Sequencing Confirms Presumed Nosocomial Transmission of Livestock-Associated Methicillin-Resistant Staphylococcus aureus in the Netherlands

Abstract: Livestock-associated methicillin-resistant Staphylococcus aureus (LA-MRSA) was detected in 2003 and rapidly became the predominant MRSA clade in the Netherlands. Studies have shown that transmissions are difficult to identify, since this MRSA variant represents a genetically homogenous clade when current typing techniques are used. Here, next-generation sequencing was performed on 206 LA-MRSA isolates to assess the capability of LA-MRSA to be transmitted between humans. The usefulness of single nucleotide vari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
15
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 37 publications
3
15
0
Order By: Relevance
“…The presence of TA system pemIK-Sa1 likely stabilizes its maintenance as the system has been demonstrated to display required properties (Bukowski et al, 2013). Conversely, homologs of group II plasmids, pRIVM4390 (pMCCL5) and pRIVM1295-2 (GenBank accessions CP013623 and CP013618), were reported recently in an opposite context, namely in livestock-associated MRSA (LA-MRSA) strains transmitted from farmed animals to humans in Netherlands, which dated back to 2003 (Bosch et al, 2016). It is noteworthy that pRIVM1295-2 found here in ph1 strain, which belongs to sequence type 1347 (ST1347) according to multilocus sequence typing (MLST, Maiden et al, 1998), was reported before by Lowder et al (2009) regarding a single human-to-poultry host jump and radiation among broiler chicken of unique to Poland, human ST5 clonal lineage that was roughly estimated to have occurred around 1970s.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The presence of TA system pemIK-Sa1 likely stabilizes its maintenance as the system has been demonstrated to display required properties (Bukowski et al, 2013). Conversely, homologs of group II plasmids, pRIVM4390 (pMCCL5) and pRIVM1295-2 (GenBank accessions CP013623 and CP013618), were reported recently in an opposite context, namely in livestock-associated MRSA (LA-MRSA) strains transmitted from farmed animals to humans in Netherlands, which dated back to 2003 (Bosch et al, 2016). It is noteworthy that pRIVM1295-2 found here in ph1 strain, which belongs to sequence type 1347 (ST1347) according to multilocus sequence typing (MLST, Maiden et al, 1998), was reported before by Lowder et al (2009) regarding a single human-to-poultry host jump and radiation among broiler chicken of unique to Poland, human ST5 clonal lineage that was roughly estimated to have occurred around 1970s.…”
Section: Discussionmentioning
confidence: 99%
“…Mass scale use of antibacterial drugs, especially in farming, increases the pressure for resistance determinants spread in natural environment and their exchange among free-living bacteria as well as animal commensals (Martinez, 2009; Fluit, 2012; He et al, 2014; Cuny et al, 2017; Kumar et al, 2017; Lau et al, 2017). Temporary colonization of humans by animal strains leading to the interaction with human microbiota or stable colonization (host jump) are not a rare phenomenon and the last part of the route (Armand-Lefevre et al, 2005; Voss et al, 2005; Bosch et al, 2016). Indeed, commensal strains of the same species or genus constitute a vast reservoir for antibiotic resistance determinants for those displaying pathogenic potential as it is observed for staphylococci (Tulinski et al, 2012; Hung et al, 2015; Morgenstern et al, 2016; Savini et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Small hospital outbreaks of MRSA ST398 have occurred, the first in a Dutch hospital in 2007, but this phenomenon is still infrequent. Nevertheless, a recent study in which the genomes of 206 LA-MRSA isolates were fully sequenced showed that transmission of LA-MRSA between humans occurs in Dutch healthcare settings [53].…”
Section: Mrsa In Food-chain Animalsmentioning
confidence: 99%
“…Instead, the isolates harbored a recombinase gene with 99% homology to ccrC6 , recently identified in a 43,922-bp SCC mec element in ST84 MRSP ( 15 ) and methicillin-resistant S. schleiferi (MRSS) ( 25 ). This element is also present in ST398 MRSA RIVM3897 ( 26 ), but the RIVM3987 element lacks the final 8,164 bp at the 3′ end of the SCC mec cassette in ST84 MRSP and MRSS. The nine isolates in this study showed 99% homology to the entire SCC mec cassette from MRSP NA45, which contained heavy metal resistance genes arsB, arsC , arsR (arsenic resistance) and copA (copper resistance) but no antimicrobial resistance genes.…”
Section: Observationmentioning
confidence: 99%